Pengaruh Model Pembelajaran Self Directed Learning Terhadap Peningkatan Kualitas Perkuliahan Fisiologi Tumbuhan Di Program Studi Pendidikan Biologi STKIP Riama Medan - Simbolon, Jimmy Francius (Unversitas Katolik Santo Thomas, 2020)
This research aims to determine the effect of the Self Directed Learning (SDL) model on improving the quality of plant physiology lectures in the Biology Education Study Program STKIP Riama Medan. The populations are students of Biology Education Study Program TA. 2013/2014 which is 20 people. The sample of the research were all members of the population in this research. The method used in this research is descriptive method with purposive sampling technique. Based on the results of the study, it is known that students have applied the Self Directed Learning (SDL) learning model with high (63%). Learning evaluation results also increased by 15% from 60% to 75%. Self Directed Learning (SDL) model is very influential on improving the quality of Plant Physiology lectures in Biology Education Study Program STKIP Riama Medan.